Utilización del método elisa en la determinación del péptido c en pacientes diabéticos atendidos en el hospital José María Velasco Ibarra de la ciudad del tena, en el período febrero-julio 2015. - Velásquez Valles, Patricia Marilin (2015)
This research aims to make the determination of C-peptide using the Elisa method, in diabetic patients treated at the hospital José María Velasco Ibarra, in the period from February to July 2015. In addition the following research aims to meet the training C-peptide levels from pancreatic beta cells. And determine the exact values ​​of C-peptide in the blood samples using the quantitative ELISA method as now can be seen a large number of patients with diabetes. The research was descriptive - correlated, including patients with possible diagnosis of diabetes mellitus. a population of 50 individuals diagnosed with diabetes mellitus, of which 48% were female gender and the remaining 52% were males in various age groups, which were conducted laboratory tests depending identified of the reference values ​​as immunoenzymometric assay technique, in the total population, using the value (0.7 to 1.9 ng / ml).